2007
DOI: 10.1103/physrevb.76.161405
|View full text |Cite
|
Sign up to set email alerts
|

Four-probe measurements of carbon nanotubes with narrow metal contacts

Abstract: We find that electrons in single-wall carbon nanotubes may propagate substantial distances ͑tens of nanom-eters͒ under metal contacts. We perform four-probe transport measurements of the nanotube conductance and observe significant deviations from the standard Kirchhoff's circuit rules. Most noticeably, injecting current between two neighboring contacts on one end of the nanotube induces a nonzero voltage difference between two contacts on the other end.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…In this model the InAs wire is considered to be divided into two sequentially connected quantum dots. The next main parameters are used to characterize this system: dot 1(2) to back-gate capacitance (C 1(2)BG ), the mutual capacitance of the dots (C m ), and the capacitance of dot 1(2) to the left(right) contact (C L(R) ), the width of the energy levels of dot 1(2) (Γ 1 (2) ). The explicit expression of dot 1(2) to tip capacitance C 1(2)t on the tip to dot distance can be found in [31].…”
Section: Methodsmentioning
confidence: 99%
“…In this model the InAs wire is considered to be divided into two sequentially connected quantum dots. The next main parameters are used to characterize this system: dot 1(2) to back-gate capacitance (C 1(2)BG ), the mutual capacitance of the dots (C m ), and the capacitance of dot 1(2) to the left(right) contact (C L(R) ), the width of the energy levels of dot 1(2) (Γ 1 (2) ). The explicit expression of dot 1(2) to tip capacitance C 1(2)t on the tip to dot distance can be found in [31].…”
Section: Methodsmentioning
confidence: 99%
“…First, the straight way passing the second contact in the outermost shell directly below the electrode. Although Ke et al [126] calculated that the transmission straight through the contact is drastically decreasing even for narrow contacts, Makarovski et al [127] and Gunnarsson et al [128] both found a non-constant non-local potential in SWCNTs indicating a non-vanishing transmission through the contact. For the MWCNT used in our experiment, an additional pathway that does not cross the contact is possible.…”
Section: Measurements In Non-local Geometrymentioning
confidence: 99%
“…Another approach for these fluctuations is given by Makarovski et al [127] and Gunnarsson et al [128]. The authors found significant voltages in four-point measurements of SWCNTs in non-local geometry and traced it back to different coupling of the probes to the two orbital modes of the tube.…”
Section: Measurements In Non-local Geometrymentioning
confidence: 99%
“…Note: After completing this work, we have become aware of a similar, but independent study by A. Makarovski et al [23].…”
mentioning
confidence: 93%
“…The dashed curve is suppressed by approximately a factor of 7 − 8. Hence, a fraction of 13 % can pass under the contact by direct transmission [23]. This is surprisingly large taken the typical values of the two-terminal resistances and the fact that the metal electrodes were evaporated directly onto a freshly CVD-grown CNT.…”
mentioning
confidence: 99%